Self-directed speech and dialogue in dementia care: the potential of co-participants' contributions. (2nd January 2019) - Lindholm, Camilla; Wide, Camilla
Abstract: Purpose: Dementia is associated with an ongoing decline in language function, involving both language production and comprehension. Maintaining a conversation with persons with dementia may be challenging. In this study, we investigate how the contributions of professional caregivers affect the linguistic contributions of the speaker with dementia. Methods: This is a conversation analytic case study of one individual with dementia. The data are drawn from a five-hour video corpus collected at a Swedish speaking care facility in Finland. Results: In comparing self-directed speech and dialogue, the results show how professional caregivers can induce change in the linguistic and interactional behaviors of a person with dementia. Conclusions: Introducing an interactional perspective to self-directed speech and dialogue, this study provides new insights into the notion of a "good conversation" in dementia care.